Covering the screw-access holes of implant restorations in the esthetic zone: a clinical report. - Abolfazl Saboury; Ali Gooya (Tehran University of Medical Sciences, 2014)
Screw-retained implant restorations have an advantage of predictable retention as well as retrievability, and obviate the risk of excessive sub-gingival cement commonly associated with cement retained implant restorations. Screw-retained restorations generally have screw access holes, which can compromise esthetics and weaken the porcelain around the holes. The purpose of this study is to describe the use of a separate overcasting crown design to cover the screw access hole of implant screw-retained prosthesis for improved esthetics.